Postgraduate Wage Premiums and the Gender Wage Gap in Canada - Waite, Sean (Canadian Journal of Higher Education, 2017)
Since the 1990s, enrolment in postgraduate programs has increased significantly in Canada. In more recent years, this has led to concerns regarding overproduction and the labour market outcomes of those with postgraduate education. Women have played an important role in this growth, but questions remain as to whether women’s progress into the highest levels of education has helped ameliorate their wage disadvantage relative to men. Using the 2011 National Household Survey, this study finds large wage premiums for completing master’s and doctoral degrees for both men and women, especially in younger cohorts; however, there are important differences by field of study. The gender wage gap is smaller for women with master’s degrees than for those with bachelor or doctoral degrees. Occupational differences account for more of the gender wage gap than field of study, suggesting that after degree completion, university-educated women sort into occupations that are lower paid than their male counterparts’.